RADOVAN IVŠIĆ – A POET OF MAD LOVE AND DREAM (1921-2009) - Šimun Musa (Hum, 2009)
The paper is written on the occasion of death of poet Radovan Ivšić, a bilingual writer (Croatian and French), who was creating noticeable works in Paris for fifty years, in the closest cooperation with A. Breton, widely and continuously working in his surrealist circle.